1996
DOI: 10.1007/bf01712246
|View full text |Cite
|
Sign up to set email alerts
|

A new side effect of inhaled nitric oxide in neonates and infants with pulmonary hypertension: Functional impairment of the neutrophil respiratory burst

Abstract: The results suggest that inhalation of NO in patients with pulmonary hypertension causes reduced superoxide anion production by neutrophils stimulated with E. coli or with fMLP. To determine the clinical importance of this systemic side effect with respect to bacterial infections, a randomized controlled study is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 34 publications
1
15
0
2
Order By: Relevance
“…This confirms and extends the results of several studies using in vitro methods of NO exposure to examine the effect of NO on neutrophils from adult animals [5][6][7][8]. Additionally, the data suggest that the depressive effect of NO on stimulated neutrophil CD18 expression is prevented by concurrent exposure to hyperoxia.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This confirms and extends the results of several studies using in vitro methods of NO exposure to examine the effect of NO on neutrophils from adult animals [5][6][7][8]. Additionally, the data suggest that the depressive effect of NO on stimulated neutrophil CD18 expression is prevented by concurrent exposure to hyperoxia.…”
Section: Discussionsupporting
confidence: 77%
“…Antioxidant enzymes have shown beneficial effects against hyperoxiainduced lung injury. Although the dose of NO used in this study is relatively high, higher doses than 50 ppm are still occasionally used in humans [8]. Also, use of nitric oxide as treatment for severe BPD has been described with treatment durations as long as three months [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contention is based on work by a number of laboratories reporting a subtle but prolonged nonadhesive, inhibitory effect of inhaled NO on neutrophils; 5 h after NO inhalation in swine caused neutrophil superoxide production to be reduced (35), an effect also reported in neonates that inhaled NO for 24-72 h (36). These effects were seen after prolonged incubation times, suggesting that NO was having a protracted inhibitory effect upon leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative burst can be altered, enhanced, or decreased by a number of substances and medical drugs such as antibiotics [36,54,55], nitric oxide [14], amphotericin B, lipid emulsions [29], and anesthetics [12,17]. It has been found that the oxidative burst is impaired during sepsis [13,32,47,53].…”
Section: Introductionmentioning
confidence: 98%